Stuck tunneled central venous catheters in children: Four cases removed by angiography assistance - Ateş, Ufuk; Yağmurlu, Aydın; Bingöl-Koloğlu, Meltem; Uçar, Tayfun; Can, Özlem Selvi; Göllü, Gülnur; Ergün, Ergun; Mammadov, Fuad; Taştekin, Nil Yaşam; Aktuğ, Tanju (The Turkish Journal of Pediatrics, 2018)
Adherent tunneled catheters can usually be removed by a surgical cut down, but in some cases the line can become stuck to the wall of the central veins. In such cases, forceful traction can cause vascular injury, or fracture of the catheter. We present four cases of fixated cuffed tunneled catheters. Three children had acute lymphoblastic leukemia and one had an immunodeficiency syndrome. All catheters were made from polyurethane. Indwelling times were 12-24 months. All patients` catheters were removed with great difficulty by trans-femoral access. The angiography-assisted technique is safe and easily-applied for the removal of stuck catheters in pediatric patients. These cases raise important questions concerning the maximum indwelling time and the choice of catheter material when implanting permanent central venous catheters (CVCs) in children.